Peer Survivors of Suicide Loss: A Phenomenological Study - Labestre, Gemma; Gayoles, Lisa Anna (Technium Social Sciences Journal, 2021)
The ultimate sufferers of suicide are those left behind. The present study aims to explore, describe, and interpret the lived experiences of peer survivors of suicide loss. This study utilized the phenomenological research design. The participants were selected based on their having experienced the phenomenon of being a peer survivor of suicide loss. Ten participants with low resiliency and who were severely distressed volunteered to participate. Individual narrative stories and interviews were utilized to gather the qualitative data for this study. Common themes for the lived experiences of being a peer survivor of suicide loss are: being confused about the reported suicide; being stunned by the suicide; questioning the act of suicide; accepting the truth of the suicide; grieving the loss of a friend; accepting the death of a friend; finding solace from friends; and experiencing growth after the trauma. Forging connections with other peer survivors of suicide loss are part of the healing process. Thus, this study demonstrates the possibility of this connection in providing a basis for school suicide intervention and postvention programs for peer survivors of suicide loss in a supportive environment. There is a scarcity of studies on how suicide loss affects the survivors in the Philippines, specifically on the grief of suicide-bereaved emerging adults, as most studies focus on suicidal thoughts and behaviors. This study contributes to the scarce literature on survivors of suicide loss in the country.